2021
DOI: 10.1101/2021.09.17.460800
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of cell segmentation methods without reference segmentations

Abstract: Cell segmentation is a cornerstone of many bioimage informatics studies. Inaccurate segmentation introduces computational error in downstream cellular analysis. Evaluating the segmentation results is thus a necessary step for developing the segmentation methods as well as choosing the most appropriate one for a certain kind of tissue or image. The evaluation process has typically involved comparison of segmentations to those generated by humans, which can be expensive and subject to unknown bias. We present he… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…Thus, challenges arise: how can users objectively evaluate individual segmentation methods for their own dataset without ground truth labels and choose the most suitable segmentation? Previous studies have suggested segmentation evaluation in absence of ground truth labels [15][16][17][18] . For example, reverse classification accuracy 15 uses segmentation results as pseudo-ground truth labels to train a new segmentation model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, challenges arise: how can users objectively evaluate individual segmentation methods for their own dataset without ground truth labels and choose the most suitable segmentation? Previous studies have suggested segmentation evaluation in absence of ground truth labels [15][16][17][18] . For example, reverse classification accuracy 15 uses segmentation results as pseudo-ground truth labels to train a new segmentation model.…”
Section: Introductionmentioning
confidence: 99%
“…Scores are computed purely probabilistically without thresholding the ensemble average to estimate the ground truth. Recent study 18 proposed an approach that seeks to evaluate cell segmentation methods by providing an objective evaluation approach based on assumptions about the desired characteristics of good cell segmentation methods. Evaluation metrics rely on the similarity between two segmentation methods and an overall segmentation quality score for each method uses the metrics for all methods with and without perturbation (i.e., added noise and downsampling).…”
Section: Introductionmentioning
confidence: 99%